Study of the processing of small diagnostic creations on a fluid sourcing by spiral survivals - Karpyk, Karpyk; Kostiuk , Nazar (Lviv Politechnic Publishing House, 2020)
The article considers the features of the drilling process where there is a change in temperature, hole diameter, and displacement relative to the axis and the impact on the tool, when machining holes with high-speed steel drills there is wear of the transverse edge which is completely rounded to create a conical surface. There is a decrease in the negative value of the front corners on the transverse edge of the decrease in axial force, which led to a decrease in the intensity of wear of the transverse edge. In order of increasing axial force, respectively, and the intensity of wear of the transverse edge, were sharpened and recommended sharpening methods that provide high performance of the drill, the greatest stability, increased drilling accuracy, as well as the lowest cutting force. The analysis of influence of technological methods and ways and equipment on accuracy and quality of deep openings of small diameter is carried out. The effects of the method of lubricating coolant supply on the tool stability and processing productivity are investigated. The analysis of processing on the metal-cutting equipment with constructive development of the device is executed. Also, the stress-strain state of the drilling process by the finite element method with the analysis of external influences on the twist drill is carried out. The results of the research substantiate and recommend technological methods that reduce the deformation of the tool and, as a consequence, increase the quality and accuracy of the dimensions of deep holes of small diameter.
Keywords: cutting process, deep drilling, deep openings processing, stability, finite element method, cutting process modeling